Semi-Synthetic Analogues of Cryptolepine as a Potential Source of Sustainable Drugs for the Treatment of Malaria, Human African Trypanosomiasis, and Cancer - Abacha, Yabalu Z.; Forkuo, Arnold Donkor; Gbedema, Stephen Y.; Mittal, Nimisha; Ottilie, Sabine; Rocamora, Frances; Winzeler, Elizabeth A.; van Schalkwyk, Donelly A.; Kelly, John M.; Taylor, Martin C.; Reader, Janette; Birkholtz, Lyn-Marie; et al. (Frontiers in Pharmacology, 2022)
The prospect of eradicating malaria continues to be challenging in the face of increasing parasite resistance to antimalarial drugs so that novel antimalarials active against asexual, sexual, and liver stage malaria parasites are urgently needed. In addition, new antimalarials need to be affordable and available to those most in need and, bearing in mind climate change, should ideally be sustainable. The West African climbing shrub, Cryptolepis sanguinolenta is used traditionally for the treatment of malaria; its principal alkaloid, cryptolepine (1) has been shown to have antimalarial properties and the synthetic analogue 2,7-dibromocryptolepine (2) is of interest as a lead towards new antimalarial agents. Cryptolepine (1) was isolated using a two-step Soxhlet extraction of C. sanguinolenta roots followed by crystallisation (yield 0.8% calculated as base with respect to the dried roots). Semi-synthetic 7-bromo- (3), 7, 9-dibromo- (4), 7-iodo- (5) and 7, 9-dibromocryptolepine (6) were obtained in excellent yield by reaction of 1 with N-bromo- or N-iodosuccinimide in trifluoroacetic acid as a solvent. All compounds were active against Plasmodia in vitro but 6 showed the most selective profile with respect to HepG2 cells: P. falciparum (chloroquine resistant strain K1), IC50 = 0.25 µM, SI = 113; late stage, gametocytes, IC50 = 2.2 µM, SI = 13; liver stage, P. berghei sporozoites IC50 = 6.13 µM, SI = 4.6. Compounds 3-6 were also active against the emerging zoonotic species P. knowlesi with 5 being the most potent (IC50 = 0.11 µM). In addition, 3-6 potently inhibited T. brucei in vitro at nM concentrations and good selectivity with 6 again being the most selective (IC50 = 59 nM, SI = 478). These compounds were also cytotoxic to wild type ovarian cancer cells as well as adriamycin-resistant and, except for 5, cisplatin-resistant ovarian cancer cells. In an acute oral toxicity test in mice, 3-6 did not exhibit toxic effects at doses of up to 100 mg/kg/dose × 3 consecutive days. This study demonstrates that C. sanguinolenta may be utilised as a sustainable source of novel compounds that may lead to the development of novel agents for the treatment of malaria, African trypanosomiasis and cancer.